2011
DOI: 10.1007/s11425-011-4346-y
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent flow modeling

Abstract: We first present multicomponent flow models derived from the kinetic theory of gases. We then investigate the symmetric hyperbolic-parabolic structure of the resulting system of partial differential equations and discuss the Cauchy problem for smooth solutions. We also address the existence of deflagration waves also termed anchored waves. We further indicate related models which have a similar hyperbolic-parabolic structure, notably the Saint-Venant system with a temperature equation as well as the equations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 79 publications
2
66
0
Order By: Relevance
“…Numerical simulations of multi-scale phenomena are commonly requested for modelling purposes in many applications such as combustion [10,31,40,49,50], chemical vapor deposition [32], or air pollution modelling [39,48,61]. The important development of the numerical strategies in these and in other fields such as nonlinear chemical dynamics for excitable media [6,20,21] or biomedical engineering [12,22,34] is mainly due to the constant increase of the computer power (see for instance [23] for a recent review of methods applied to turbulent combustion).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations of multi-scale phenomena are commonly requested for modelling purposes in many applications such as combustion [10,31,40,49,50], chemical vapor deposition [32], or air pollution modelling [39,48,61]. The important development of the numerical strategies in these and in other fields such as nonlinear chemical dynamics for excitable media [6,20,21] or biomedical engineering [12,22,34] is mainly due to the constant increase of the computer power (see for instance [23] for a recent review of methods applied to turbulent combustion).…”
Section: Introductionmentioning
confidence: 99%
“…In [15,Section 7.7.1], the matrix with elements −a ij c j is analyzed and it is shown that it is symmetric, positive semi-definite, irreducible, and a singular M-matrix as well as that a generalized inverse can be defined. Our approach is to apply the Perron-Frobenius theory to A, following [4].…”
Section: Properties Of the Diffusion Matricesmentioning
confidence: 99%
“…For more general expressions of d i , we refer to [15,Chapter 7]. The chemical potential under isothermal, isobaric conditions is defined by µ i = ∂G/∂c i , where G is the Gibbs free energy.…”
Section: Appendix a Derivation Of The Maxwell-stefan Relationsmentioning
confidence: 99%
See 2 more Smart Citations